EVALUATION OF EFFICACY, INTRAUTERINE SAFETY AND STORAGE CONDITIONS OF LUGOL'S IODINE - SOOD, PANKAJ; THAKUR, S D; SARVESH,; DOGRA, V; VASISHTA, N K; SINGH, M M; GANDOTRA, V K (The Indian Journal of Animal Reproduction, 2023)
Different concentrations of Lugol's iodine [I 2KI] have been utilized to treat endometritis with variable successrates in cows. In present study, intrauterine infusion of 30 ml of 0.3% I2KI during estrus and one day later revealeda therapeutic success rate of 56.2% in 16 cycling cows with moderate moderate/severe clinical endometritis. Thecows not responding tended to have a greater magnitude of uterine microbial load before treatment. The sameprotocol investigated in another set of six cows with healthy uterus revealed a normal endometrial histology in theestrus succeeding l2KI infusion, thereby suggesting the said protocol to be safe .. In another part of study, I2KIstored in transparent or dark glass containers for a period of 6 months and exposed to illumination intensity of69.5 ± 2.3 lux did not affect the in vitro antibacterial activity. However, an air exposure for 72 h significantly reducedthe optical density and in vitro antibacterial activity.
Keywords: Cattle; Endometritis; Lugol's iodine; Storage